Homens benificiários do programa bolsa família: pobreza, formação das masculinidades e sua interface no cotidiano familiar. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
This study aims to understand the daily life of families with male leadership, beneficiaries of the Federal Bolsa Família Programme. The research seeks to identify the interfaces of masculinity formation in families whose father is responsible for care, education and maintenance of their children. Its research locus is the Bolsa Família Programme, being significant subjects, the beneficiaries of the programme, and residents in the Campos Gerais - PR Region. Family vulnerabilities and survival strategies of this population layer will be entered, who is in poverty situation. The research is quantitative-qualitative nature, using data from CADÚNICO, of Federal Government. Analysis corresponding to the municipalities of Campos Gerais - PR and the beneficiaries of the Programme, as well as semi-structured interviews were used as a data collection tool. Studying the masculinities category made it uncover behaviors and actions regarding the ways of acting and thinking about sexual roles and hierarchy in the family. The study allows visibility to heterosexual men who do not correspond to the current hegemonic image, even having masculinity as a reference to be followed. The research reveals that the family can mean a place of protection and aggregation of values and feelings, as well as may mean a place of social lack of protection and violation of rights. It is pointed to the existence of the demand of a father more participatory and involved in raising children, with some limitations regarding issues pertaining to the female body and sexuality. On the other hand, these men are breaking the standards established by society in relation to gender standard, with new ways of exercising parenthood and care for offspring.
Keywords: Família; Masculinidades; Pobreza; Family; Masculinities; Poverty; CNPQ::CIENCIAS SOCIAIS APLICADAS